Case report: MR-guided laser induced thermal therapy for palliative cingulotomy - Allam, Anthony K.; Larkin, M. Benjamin; Katlowitz, Kalman A.; Shofty, Ben; Viswanathan, Ashwin (Frontiers in Pain Research, 2022)
In end-stage cancer, oncologic pain refractory to medical management significantly reduces patients’ quality of life. In recent years, ablative surgery has seen a resurgence in treating diffuse and focal cancer pain in terminal patients. The anterior cingulate gyrus has been a key focus as it plays a role in the cognitive and emotional processing of pain. While radiofrequency ablation of the dorsal anterior cingulate is well described for treating cancer pain, MRI-guided laser-induced thermal therapy (LITT) is novel. Our paper describes a patient treated with an MRI-guided LITT therapy of the anterior cingulate gyrus for intractable debilitating pain secondary to terminal metastatic cancer.